1995
DOI: 10.1007/bf00032003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microcystis aeruginosa on interference competition between Daphnia pulex and Keratella cochlearis

Abstract: Laboratory experiments tested the hypothesis that a toxic strain of Microcystis aeruginosa decreases the ability of Daphnia pulex to interfere with Keratella cochlearis . To test a variety of conditions, juvenile and adult Daphnia were exposed to the cyanobacterium for different time periods prior to, and during the experiments . Adult Daphnia not only suppressed rotifers over successive two-day intervals, but also had a significant impact within a 24-hour period . However, the presence of Microcystis (5 x 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The cladoceran data from L. Peipsi and in L. Võ rtsjä rv (Table 2, 3; Fig 3) suggest that cladocerans consume more algae in L. Peipsi than in L. Võ rtsjä rv. The food ration of cladocerans is determined directly by mean cladoceran weight; feeding efficiency is proportional to body size (Carpenter & Kitchell, 1992;Sartonov, 1995). Correlation analysis has revealed a positive relationship between mean cladoceran weight and grazing activity for both studied lakes (L. Peipsi: r = 0.6, L. Võ rtsjä rv: r = 0.4, P < 0.0001; Haberman & Nõ ges, 2003).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The cladoceran data from L. Peipsi and in L. Võ rtsjä rv (Table 2, 3; Fig 3) suggest that cladocerans consume more algae in L. Peipsi than in L. Võ rtsjä rv. The food ration of cladocerans is determined directly by mean cladoceran weight; feeding efficiency is proportional to body size (Carpenter & Kitchell, 1992;Sartonov, 1995). Correlation analysis has revealed a positive relationship between mean cladoceran weight and grazing activity for both studied lakes (L. Peipsi: r = 0.6, L. Võ rtsjä rv: r = 0.4, P < 0.0001; Haberman & Nõ ges, 2003).…”
mentioning
confidence: 89%
“…Dodson & Frey (2001) have found that most cladocerans prefer algae in the size range from 5 to 35 lm. The larger is the grazer, the more efficient is its grazing (Sartonov, 1995;Meijer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There are several possible hypotheses for this. Firstly, large colonial or filamentous cyanobacteria may be too large for rotifers to ingest, and hence, the inhibitory effect of Microcystis aeruginosa endotoxin could be lessened (Gilbert 1990, Sartonov 1995. Secondly, in nature other potentially nutritious food sources are closely associated with M. aeruginosa colonies, including bacteria, protozoans (Paerl 1984b), and eukaryotic algae (Kilham et al 1986) which can be consumed by rotifers.…”
Section: Introductionmentioning
confidence: 99%
“…Jungamnn, 1992;DeMott, 1999). Keratella cochlearis was superior in competition with D. pulex under toxic Microcystis (Sartonov, 1995). However, there is little or no evidence for lethal effects of toxic cyanobacteria on crustacean plankton in the field (Haney, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, including concentration, size, Microcystis toxin and alternative food abundance during blooms may result in zooplankton shifts (Jarvis et al, 1987;Fulton & Paerl, 1988;Sartonov, 1995;Chen & Xie, 2003, 2004. Different responses of species to these factors result in observed zooplankton community structure.…”
Section: Introductionmentioning
confidence: 99%